Preparation method of spheroidal graphite cast iron metallographic sample

Through the multi-step grinding, polishing and corrosion process, the problem of irregular spherical graphite dispersion and ferrite tissue contamination during the grinding process of ductile cast iron samples is solved, and the complete tissue structure and clean surface of the sample is realized, which is suitable for observation and analysis of material research.

CN119688423APending Publication Date: 2025-03-25PANZHIHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411922988.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

During the grinding process, the spherical graphite is irregularly dispersed, and the ferrite tissue is contaminated, resulting in incomplete tissue structure and uneven polishing and corrosion processes.

Method used

The multi-step grinding, polishing and corrosion process is adopted, including grinding on 180 mesh-1200 mesh sandpaper, two-stage polishing and corrosion steps using reagent A and nitric acid alcohol solutions to ensure the detection surface of the ductile iron sample is clean and complete.

Benefits of technology

Through this method, the detection surface of the ductile iron sample can keep the ball mill undispersed, the ferrite tissue is neat and pollution-free, and its complete tissue structure is obtained, which is convenient for observation and research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119688423A_ABST
    Figure CN119688423A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a spheroidal graphite cast iron metallographic sample in the technical field of metallographic tests, which comprises the following steps: S1, grinding: sequentially grinding the detection surface of the spheroidal graphite cast iron sample on abrasive paper of 180-1200 meshes; s2, polishing: in the first stage, placing the detection surface of the ground nodular cast iron sample at a preset position, close to the outer ring side, of polishing cloth, positioning and polishing, and adding water for washing; in the second stage, the detection surface of the nodular cast iron sample subjected to the first stage is placed at a preset position, close to the center, of polishing cloth, the nodular cast iron sample is driven to be circumferentially looped on the polishing cloth, and the looping directions are opposite; s3, corrosion: dripping a preset amount of reagent A on the detection surface of the polished nodular cast iron sample, wiping the detection surface of the nodular cast iron sample by using a cotton ball soaked with the reagent A, wiping the detection surface of the nodular cast iron sample by using a cotton ball soaked with a 4% nitric acid alcohol solution until the surface structure of the detection surface is clear, and then, carrying out corrosion. And the detected surface is directly dried by cold air after being washed by water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallographic testing, and in particular to a method for preparing a ductile iron metallographic sample. Background Art

[0002] In order to study the structure, composition and related properties of ductile iron, the metallographic preparation and observation and analysis of ductile iron has always been an important method in materials research.

[0003] At present, the tissues prepared by the traditional grinding method will have problems such as spherical graphite dispersion, black and blurred tissues caused by ferrite contamination, and incomplete ductile iron tissue structure. Due to excessive force, too much water added during the polishing process, or too long water washing time during the corrosion process, the spherical graphite is dispersed and presents an irregular polygonal shape. The spherical graphite dispersion leaves stains on the white ferrite, or the sample is not cleaned during the polishing and corrosion process. At the same time, the corrosion process is not enough time or the time is too long, resulting in uneven corrosion and unclear ferrite tissue structure. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the technical problem to be solved by the present invention is: how to grind ductile iron quickly and keep the ball milling non-dispersed, the ferrite structure clean and pollution-free, and obtain its complete organizational structure.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] The preparation method of the ductile iron metallographic sample includes the following steps: the grinding time is reduced as the number of sandpaper meshes increases, the polishing is performed at a preset position, the circumferential polishing is performed, and the test surface of the ductile iron sample is directly wiped with pure alcohol.

[0007] S1: grinding, grinding the test surface of the ductile iron sample on sandpaper with 180 mesh to 1200 mesh in sequence;

[0008] S2: polishing, including the first stage and the second stage. The first stage is to place the test surface of the ground ductile iron sample at a preset position near the outer ring side of the polishing cloth for positioning and polishing, and add a preset amount of water for flushing during the process; the second stage is to place the test surface of the ductile iron sample that has completed the first stage at a preset position near the center of the polishing cloth, and drive the ductile iron sample to circle circumferentially on the polishing cloth, and the circling direction is opposite to the rotation direction of the polishing machine;

[0009] S3: Corrosion. Drop a preset amount of reagent A on the test surface of the ductile iron sample that has completed the polishing step, then wipe the test surface of the ductile iron sample with a cotton ball soaked in reagent A, and then wipe the test surface of the ductile iron sample with a cotton ball soaked in 4% nitric acid alcohol solution until the surface structure of the test surface is clear, rinse with water and then directly dry the test surface with cold air.

[0010] Furthermore, in step S1, six kinds of sandpaper are selected in sequence, namely 180 mesh, 400 mesh, 600 mesh, 800 mesh, 1000 mesh and 1200 mesh, and the grinding time on each sandpaper is 80-110s, 80-100s, 60-80s, 45-60s, 30-45s, and 20-30s respectively, and the whole grinding process lasts 6-8min.

[0011] Furthermore, the grinding process of the test surface of the ductile iron sample on sandpaper of any mesh size is as follows: the test surface of the ductile iron sample is contacted with the sandpaper surface with a preset force and pushed linearly in one direction for 20cm-30cm, and repeated 4-10 times until the direction of the scratches on the surface of the sample is consistent and there is no cross-section, and then the sample is rotated 90° and placed on the next sandpaper of the same mesh size to repeat the above action, and the scratches left by the previous sandpaper are ground off to complete a grinding cycle. After multiple grinding cycles, when the grinding time of the sandpaper of the above mesh size is reached, the sandpaper of the next mesh size is replaced and the grinding cycle is re-entered.

[0012] Furthermore, in step S2, before starting the first stage, W2.5 water-soluble abrasive paste is evenly applied on the polishing cloth, and the speed of the polishing machine is adjusted to 800-1200 rpm.

[0013] Furthermore, in the first stage, the test surface of the ground ductile iron sample is placed at a preset position on the polishing cloth close to the outer ring side for positioning and polishing for 60s-90s, and then the test surface is rinsed with water, and the above process is repeated 3-5 times.

[0014] Furthermore, in the above second stage, the test surface of the ductile iron sample is placed in front of the polishing cloth at a preset position close to the center, and a preset amount of water is added to the polishing cloth; and during the circling process, if the sample is observed to be hot, water is added for 90s-120s.

[0015] Furthermore, the above-mentioned reagent A includes alcohol.

[0016] Furthermore, in step S3, a cotton ball soaked in reagent A is used to wipe the test surface of the ductile iron sample for a duration greater than 5 seconds, and the above process is repeated once after completion.

[0017] Further, wipe the test surface of the ductile iron sample with a cotton ball soaked in 4% nitric acid alcohol solution for 10s-13s. When the surface structure is clear, rinse it quickly with water for 1 second after wiping, then quickly drip 2-3 tubes of reagent A, and then blow dry the test surface of the ductile iron sample with cold air from a hair dryer.

[0018] The beneficial effects of the present invention are:

[0019] Through the first and second stage polishing processes, it is ensured that the scratches on the test surface of the ductile iron sample are worn away, and the ball milling is kept undispersed, and the ferrite structure is neat and pollution-free. Then, the sample test surface is wiped successively with reagent A and nitric acid alcohol solution, and water is not added to clean the sample surface to avoid the spherical graphite being washed away by water and the ferrite structure being dirty. Wiping the sample surface with reagent A can keep the spherical graphite intact while ensuring the cleanness of the ferrite structure. At the same time, it is not easy to scratch the ductile iron when wiping it, so as to obtain its complete organizational structure, which is convenient for observation and research. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a flow chart of the method of the present invention;

[0021] Figure 2 This is a topographic image of the metallographic sample inspection surface prepared in an embodiment of the present invention; DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with the accompanying drawings.

[0023] The present application embodiment proposes a method for preparing a ductile iron metallographic sample, comprising the following steps:

[0024] S1: grinding, grinding the test surface of the ductile iron sample on a variety of sandpapers ranging from 180 mesh to 1200 mesh in sequence; in step S1, six kinds of sandpaper are selected in sequence, namely 180 mesh, 400 mesh, 600 mesh, 800 mesh, 1000 mesh and 1200 mesh, and the grinding time on each sandpaper is 80-110s, 80-100s, 60-80s, 45-60s, 30-45s, 20-30s in sequence, and the whole grinding process lasts 6-8min.

[0025] Specifically, the grinding process of the detection surface of the ductile iron sample on the sandpaper of any mesh size is as follows: the detection surface of the ductile iron sample is contacted with the sandpaper surface with a preset force and pushed linearly in one direction for 20cm-30cm, and repeated 4-10 times until the direction of the scratches on the surface of the sample is consistent and there is no cross-section, and then the sample is rotated 90° and placed on the next sandpaper of the same mesh size to repeat the above action, and the scratches left by the previous sandpaper are ground off to complete a grinding cycle. After multiple grinding cycles, when the grinding time of the sandpaper of the above mesh size is reached, the sandpaper of the next mesh size is replaced and the grinding cycle is re-entered. The whole process lasts for 6-8 minutes. Through multiple grinding cycles and the grinding process of sandpaper of various mesh sizes, the ductile iron detection surface can be effectively and fully polished, and in the process of grinding layer by layer, the mesh size of the sandpaper increases from small to large, and the scratches of the previous layer can be continuously ground off, and the wear marks become smaller and smaller, which is convenient for the subsequent polishing process to completely remove the wear marks.

[0026] S2: Polishing, including the first stage and the second stage. The first stage is to place the test surface of the ground ductile iron sample at a preset position near the outer ring side of the polishing cloth for positioning and polishing. During the process, a preset amount of water is added for flushing, specifically one tenth of the capacity of a standard washing bottle; the second stage is to place the test surface of the ductile iron sample that has completed the first stage at a preset position near the center of the polishing cloth, and drive the ductile iron sample to circle circumferentially on the polishing cloth, and the circling direction is opposite to the rotation direction of the polishing machine; before the polishing process, firstly stick the polishing cloth flatly on the polishing machine, clean the surface of the polishing cloth with water, turn on the polishing machine to throw away the water and then turn it off, then evenly apply W2.5 water-soluble abrasive paste on the polishing cloth, and then turn on the polishing machine for polishing, adjust the speed to 800-1200 rpm, and turn the direction to reverse Hour hand, enter the first stage, hold the sample firmly with your hand, gently press it on the outer periphery of the rotating polishing cloth for polishing, keep this posture unchanged, the sample does not rotate, control the time within 60-90 seconds, then quickly take out the sample and rinse it with water, and the amount of rinse water should not be too large to prevent the spherical graphite from being dispersed, and then repeat this action 3-5 times, each time lasting 90-120 seconds; after the first stage is completed, add a small amount of water to the polishing cloth, place the ductile iron sample close to the center of the polishing cloth, hold the sample firmly with your hand and place it in the middle of the polishing machine for polishing, turn in circles against the direction of rotation of the polishing machine, apply force steadily and evenly, and the force should be appropriate without excessive pressure. When the sample is hot, rinse it gently with water. This step is conducive to removing scratches of different degrees, repeat this action, each time lasting 90-120 seconds.

[0027] Through the first stage of positioning polishing, the wear marks on the ductile iron test surface are gradually removed through the friction between the polishing cloth and the polishing paste. In the process, foreign matter on the test surface can be cleaned up, making the structure of the test surface clearer. At the same time, in the second stage, the polishing cloth is circled in the reverse direction near the center, which can effectively remove the residual wear marks and the polishing marks produced in the first stage, thereby improving the sample quality.

[0028] S3: Corrosion. Drop a preset amount of reagent A on the test surface of the ductile iron sample that has completed the polishing step, then wipe the test surface of the ductile iron sample with a cotton ball soaked in reagent A, and then wipe the test surface of the ductile iron sample with a cotton ball soaked in 4% nitric acid alcohol solution until the surface structure of the test surface is clear, rinse with water and then directly dry the test surface with cold air.

[0029] Specifically, quickly drip 2-3 tubes of reagent A onto the freshly polished sample, then use a clamp to hold a cotton ball, drip reagent A onto it until reagent A seeps out of the cotton, then use the cotton ball to wipe the surface of the sample with moderate force, wipe for more than 5 seconds, and repeat this action once after completion. Then use a clamp to hold a cotton ball, drip 4% nitric acid alcohol solution onto the cotton until the cotton is penetrated, then wipe the surface of the sample evenly for 10-13 seconds, and observe that the surface structure is clear. After wiping, quickly rinse with water for 1 second, then quickly drip 2-3 tubes of reagent A, and then use a hair dryer with cold air to dry the surface of the sample. The whole process lasts 90-120 seconds. Do not add water to clean the surface of the sample to prevent the spherical graphite from being dispersed by water and the ferrite structure from being dirty. Wiping the surface of the sample with reagent A can keep the spherical graphite intact while ensuring that the ferrite structure is clean. At the same time, it is not easy to scratch when wiping ductile iron, and finally form something like Figure 2 The sample diagram shown can provide its complete organizational structure for easy observation and research.

Claims

1. A method for preparing a metallographic sample of ductile iron, characterized in that: The following steps are involved: S1: grinding, grinding the test surface of the ductile iron sample on various sandpapers ranging from 180 mesh to 1200 mesh in sequence; S2: polishing, including the first stage and the second stage. The first stage is to place the test surface of the ground ductile iron sample at a preset position on the polishing cloth close to the outer ring side for positioning and polishing, and add a preset amount of water for flushing during the process; The second stage is to place the test surface of the ductile iron sample that has completed the first stage at a preset position close to the center of the polishing cloth, and drive the ductile iron sample to circle circumferentially on the polishing cloth, and the circle direction is opposite to the rotation direction of the polisher; S3: Corrosion. Drop a preset amount of reagent A on the test surface of the ductile iron sample that has completed the polishing step, then wipe the test surface of the ductile iron sample with a cotton ball soaked in reagent A, and then wipe the test surface of the ductile iron sample with a cotton ball soaked in 4% nitric acid alcohol solution until the surface structure of the test surface is clear, rinse with water and then directly dry the test surface with cold air.

2. The method for preparing a ductile iron metallographic sample according to claim 1, characterized in that: In step S1, six kinds of sandpaper are selected in sequence, namely 180 mesh, 400 mesh, 600 mesh, 800 mesh, 1000 mesh and 1200 mesh. The grinding time on each sandpaper is 80-110s, 80-100s, 60-80s, 45-60s, 30-45s, and 20-30s respectively, and the whole grinding process lasts 6-8min.

3. The method for preparing a ductile iron metallographic sample according to claim 2, characterized in that: The grinding process of the detection surface of the ductile iron sample on the sandpaper of any mesh size is as follows: the detection surface of the ductile iron sample is brought into contact with the sandpaper surface with a preset force and is linearly pushed 20cm-30cm in one direction, and this is repeated 4-10 times until the direction of the scratches on the surface of the sample is consistent and there is no fracture, and then the sample is rotated 90° and placed on the next sandpaper of the same mesh size to repeat the above action, so as to grind off the scratches left by the previous sandpaper and complete a grinding cycle. After multiple grinding cycles, when the grinding time of the sandpaper of the above mesh size is reached, the sandpaper of the next mesh size is replaced and the grinding cycle is re-entered.

4. The method for preparing a ductile iron metallographic sample according to claim 1, characterized in that: In step S2, before starting the first stage, W2.5 water-soluble abrasive paste is evenly applied on the polishing cloth, and the speed of the polishing machine is adjusted to 800-1200 rpm.

5. The method for preparing a ductile iron metallographic sample according to claim 4, characterized in that: In the first stage, the test surface of the ground ductile iron sample is placed at a preset position on the polishing cloth close to the outer ring side for positioning and polishing for 60s-90s, and then the test surface is rinsed with water, and the above process is repeated 3-5 times.

6. The method for preparing a ductile iron metallographic sample according to claim 4, characterized in that: In the second stage, the test surface of the ductile iron sample is placed in front of the polishing cloth at a preset position close to the center, and a preset amount of water is added to the polishing cloth; and during the circling process, if the sample is observed to be hot, water is added for 90s-120s.

7. The method for preparing a ductile iron metallographic sample according to claim 1, characterized in that: The A reagent includes pure alcohol.

8. The method for preparing a ductile iron metallographic sample according to claim 1, characterized in that: In step S3, a cotton ball soaked in reagent A is used to wipe the test surface of the ductile iron sample for a duration of more than 5 seconds, and the above process is repeated once after completion.

9. The method for preparing a ductile iron metallographic sample according to claim 8, characterized in that: Wipe the test surface of the ductile iron sample with a cotton ball soaked in 4% nitric acid alcohol solution for 10s-13s. When the surface structure is clear, rinse it quickly with water for 1 second, then quickly drip 2-3 tubes of reagent A, and then blow dry the test surface of the ductile iron sample with cold air from a hair dryer.